1999
DOI: 10.1021/jf990440d
|View full text |Cite
|
Sign up to set email alerts
|

Flavonol Glycosides from Montcalm Dark Red Kidney Bean:  Implications for the Genetics of Seed Coat Color in Phaseolus vulgaris L.

Abstract: Three flavonol glycosides were isolated and identified from the commercial dark red kidney bean (Phaseolus vulgaris L.) cultivar Montcalm. In order of highest to lowest concentration these compounds were 3',4',5,7-tetrahydroxyflavonol 3-O-beta-D-glucopyranosyl (2-->1) O-beta-D-xylopyranoside (compound 1), quercetin 3-O-beta-D-glucopyranoside (compound 2), and kaempferol 3-O-beta-D-glucopyranoside (compound 3). Compound 1 is a flavonol glycoside that has not been reported before in P. vulgaris L. These three fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 7 publications
1
37
0
Order By: Relevance
“…The identification of compound 2 was confirmed by the injection of authentic standard and by comparison of their retention times and spectral data. These findings were in agreement with several literature data reporting the presence of kaempferol 3-O-glucoside [22,23,36,37] and kaempferol 3-acetylglucoside [22] in various Phaseolus genotypes.…”
Section: Identification Of Functional Compounds In Selected Accessionssupporting
confidence: 93%
“…The identification of compound 2 was confirmed by the injection of authentic standard and by comparison of their retention times and spectral data. These findings were in agreement with several literature data reporting the presence of kaempferol 3-O-glucoside [22,23,36,37] and kaempferol 3-acetylglucoside [22] in various Phaseolus genotypes.…”
Section: Identification Of Functional Compounds In Selected Accessionssupporting
confidence: 93%
“…It has been reported that higher condensed tannins or proanthocyanidin content are seen in colored beans than in pale (in yellow and white) colored beans (Beninger & Hosfield, 1999). However, Cardador-Martinez, Loarca-Pina, and Oomah, 2002 suggested that the highest antioxidant activity in white seeds might be due to their condensed tannin content.…”
Section: Discussionmentioning
confidence: 96%
“…Seed coat pigment in the brown-seeded line of Brassica consisting of proanthocyanidins (condensed tannins). The normally colorless proanthocyanidins undergo secondary changes during seed maturation to form oxidized complexes with the cell wall, polysaccharides and other phenolics in the seed coat, causing it to darken (Beninger & Hosfield, 1999;Marles, Gruber, Scoles, & Muir, 2003). The mean value of a* attribute was negative in all cases, indicating the presence of green color.…”
Section: Surface Color Analysis Of From Particular Fractionsmentioning
confidence: 90%